The prevalence, clinical and pathological characteristics of primary focal segmental glomerulosclerosis in Turkish adults: The data from TSN-Gold (Turkish society of nephrology glomerular diseases) working group - Kurultak, İlhan; Güngör, Özkan; Öztürk, Savaş; Dirim, Ahmet Burak; Eren, Necmi; Yenigün, Ezgi; Ahbap Dal, Elbis; Dinçer, Mevlüt Tamer; Bora, Feyza; Akgür, Suat; Şumnu, Abdullah; Dursun, Belda; et al. (Oxford University Press, 2020)
[Abstract Not Available]
Keywords: TSN-Gold; Clinical and Pathological Characteristics; Nephrology Glomerular Diseases